2020
DOI: 10.1097/bsd.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Liposomal Bupivacaine Decreases Length of Stay and Opioid Usage Following Lumbar Spinal Fusion

Abstract: Study Design: A retrospective cohort review. Objectives: The objective of this study was to investigate the efficacy of liposomal bupivacaine (LB) in patients undergoing lumbar spinal fusion. Summary of Background Data: Historically, posterior spinal fusion has been recognized as a particularly painful surgery. Postoperative pain limits early patient mobilization and discharge, and negatively impacts patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…14,26,37,40 Despite its higher cost, 2 studies comparing LB and a nonliposomal local anesthetic in lumbar fusion surgery demonstrated overall health care cost savings when utilizing LB. 40,43 These cost savings were most likely because of both studies finding a significant decrease in LOS for patients that received LB. Another retrospective study comparing the efficacy of bupivacaine alone versus LB when managing posterior cervical and lumbar decompression and fusions found that patients receiving bupivacaine alone required approximately twice the number of narcotics in the perioperative period compared with the LB cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,26,37,40 Despite its higher cost, 2 studies comparing LB and a nonliposomal local anesthetic in lumbar fusion surgery demonstrated overall health care cost savings when utilizing LB. 40,43 These cost savings were most likely because of both studies finding a significant decrease in LOS for patients that received LB. Another retrospective study comparing the efficacy of bupivacaine alone versus LB when managing posterior cervical and lumbar decompression and fusions found that patients receiving bupivacaine alone required approximately twice the number of narcotics in the perioperative period compared with the LB cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of a 20 ml (266 mg) vial of LB is usually between $280 and $350, while the cost of using bupivacaine alone is typically between $2 and $8 14,26,37,40. Despite its higher cost, 2 studies comparing LB and a nonliposomal local anesthetic in lumbar fusion surgery demonstrated overall health care cost savings when utilizing LB 40,43. These cost savings were most likely because of both studies finding a significant decrease in LOS for patients that received LB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liposomal bupivacaine (LB) is a long-acting multivesicular formation of the local anesthetic that allows for prolonged release over several days 9 . It has been shown to be effective in decreasing postoperative opioid requirements and improving postoperative pain in adults who undergo orthopedic and spine procedures when used at the time of surgery 10–13 . It also has been safely used in the pediatric population and recently gained FDA approval 14,15 .…”
mentioning
confidence: 99%